Perceptions of medical students and their facilitators on clinical communication skills teaching, learning, and assessment - Dewi, Sari Puspa; Wilson, Amanda; Duvivier, Robbert; Kelly, Brian; Gilligan, Conor (Frontiers in Public Health, 2023)
Despite various efforts to develop communication skills in the classroom, the transfer of these skills into clinical practice is not guaranteed. This study aimed to identify barriers and facilitators of transferring communication skills from the classroom to clinical environments. A qualitative study was conducted at one Australian medical school to explore the experiences and perceptions of facilitators and students in relation to teaching and learning clinical communication skills. Thematic analysis was used to analyze data. Thirteen facilitators and sixteen medical students participated in semi-structured interviews and focus-group discussions, respectively. Primary themes included the value of teaching and learning, alignment between approaches to teaching and actual clinical practices and students' perceptions of practice, and challenges in different learning environments. This study reinforces the value of teaching and learning communication skills by facilitators and students. Classroom learning provides students with a structure to use in communicating with real patients, which can be modified to suit various situations. Students have limited opportunities, however, to be observed and receive feedback on their real-patient encounters. Classroom session that discussed communication skills experiences during clinical rotation is recommended to strengthen learning both the content and process of communication skills as well as transitioning to the clinical environment.